Quality of life of older adults in two contrasting neighbourhoods in Accra, Ghana. (February 2021) - Alaazi, Dominic A.; Menon, Devidas; Stafinski, Tania; Hodgins, Stephen; Jhangri, Gian
Highlights: Older slum and non-slum respondents reported similar QoL scores. Social supports can mitigate the impacts of poor environmental conditions on QoL. Sociodemographic factors play a critical role in determining QoL of older adults. The findings refute existing discourses portraying slums as unhealthy places. Abstract: As is the case elsewhere in sub-Saharan Africa, Ghana is experiencing a rapid increase in the population of older adults. Despite their rising numbers, the living conditions and wellbeing of older Ghanaians remain woefully understudied. This paper presents the results of a study exploring the quality of life (QoL) of older adults in two contrasting neighbourhoods in Accra, Ghana. The objectives of the study were to: (1) explore and compare the QoL of older slum and non-slum dwellers in Ghana; and (2) determine the extent of QoL disparities between slum and non-slum older adults. To accomplish these objectives, we undertook a cross-sectional survey of older adults (N = 603) residing in a slum and non-slum neighbourhood. QoL was self-assessed in four domains – physical, psychological, social, and environment – using the World Health Organization (WHO) QoL assessment tool (WHOQoL-BREF). Multivariable linear regression analyses of the data revealed no statistically significant difference between the slum and non-slum respondents in physical (coeff: 0.5; 95% CI: -1.7, 2.8; p = 0.642) and psychological (coeff: -0.2; 95% CI: -3.0, 2.6; p = 0.893) QoL. However, the slum respondents reported significantly higher social QoL than the non-slum respondents (coeff: -3.2; 95% CI: -5.6, -0.8; p = 0.010), while the reverse was true in environmental QoL (coeff: 4.2; 95% CI: 2.3, 6.2; p < 0.001). The existence of strong social support systems in the slum and better housing and neighbourhood environmental conditions in the non-slum may have accounted for the observed variation in social and environmental QoL. Thus, contrary to popular discourses that vilify slums as health-damaging milieus, these findings offer a more nuanced picture, and suggest that some features of slums may constitute important health resources for older adults.